Inhalational versus Intravenous Induction of Anesthesia in Children with a High Risk of Perioperative Respiratory Adverse Events - Ramgolam, A.; Hall, Graham; Zhang, G.; Hegarty, M.; von Ungern-Sternberg, B. (Lippincott Williams and Wilkins, 2018)
BACKGROUND: Limited evidence suggests that children have a lower incidence of perioperative respiratory adverse events when intravenous propofol is used compared with inhalational sevoflurane for the anesthesia induction. Limiting these events can improve recovery time as well as decreasing surgery waitlists and healthcare costs. This single center open-label randomized controlled trial assessed the impact of the anesthesia induction technique on the occurrence of perioperative respiratory adverse events in children at high risk of those events. METHODS: Children (N = 300; 0 to 8 yr) with at least two clinically relevant risk factors for perioperative respiratory adverse events and deemed suitable for either technique of anesthesia induction were recruited and randomized to either intravenous propofol or inhalational sevoflurane. The primary outcome was the difference in the rate of occurrence of perioperative respiratory adverse events between children receiving intravenous induction and those receiving inhalation induction of anesthesia. RESULTS: Children receiving intravenous propofol were significantly less likely to experience perioperative respiratory adverse events compared with those who received inhalational sevoflurane after adjusting for age, sex, American Society of Anesthesiologists physical status and weight (perioperative respiratory adverse event: 39/149 [26%] vs. 64/149 [43%], relative risk [RR]: 1.7, 95% CI: 1.2 to 2.3, P = 0.002, respiratory adverse events at induction: 16/149 [11%] vs. 47/149 [32%], RR: 3.06, 95% CI: 1.8 to 5.2, P < 0.001). CONCLUSIONS: Where clinically appropriate, anesthesiologists should consider using an intravenous propofol induction technique in children who are at high risk of experiencing perioperative respiratory adverse events. VISUAL ABSTRACT: An online visual overview is available for this article at http://links.lww.com/ALN/B725.